THE ROLE OF UNIVERSITY SPORTS IN STUDENTS' SOCIALIZATION AND ACADEMIC PERFORMANCE (International conference on multidisciplinary science, 2025)
This article examines the role of sports in universities as a social phenomenon and its impact on the student community and society as a whole. It analyzes aspects of socialization, the influence of sports on academic performance, personal development, and students' health. Special attention is given to the role of sports in shaping traditions and strengthening social ties. Government programs supporting student sports are also considered.